The quality, type and time spent in child care in the first three years of life and children’s cognitive and socio-emotional development at school entry - Gialamas, A (My University, 2015)
Background: Evidence from decades of research suggests that children’s experiences before starting school are crucial foundations for learning and behaviour across the life course. During the preschool years, children spend a large proportion of their time both in the family home and in the non-parental child care environment. The family home and non-parental child care settings are the key caregiving environments where infants and toddlers learn and build healthy relationships prior to commencing school. Previous research, mainly from the USA, suggests that the type, time and quality of child care influences children’s development, but there is little or no information describing the effects of these different aspects of child care on children’s development within the Australian context. Aim: The overarching aim of this thesis was to investigate the association between the type, time and quality of child care experienced by infants (0-1 years) and toddlers (2-3 years) and these children’s cognitive (receptive vocabulary, task attentiveness, academic literacy and maths proficiency) and socio-emotional development (emotional regulation, internalising and externalising behaviours) when they started school (aged 4-5 and 6-7). Specifically the aims were: • To determine whether the total amount of time spent in child care through the first three years of life was associated with children’s cognitive and socio-emotional development at age 4-5 years and whether this association varied according to the primary type of child care; • To determine whether the quality of formal child care at age 2-3 years was associated with children’s cognitive and socio-emotional development at age 4-5 and 6-7 years; • To establish if higher quality child care was associated with better cognitive and socio-emotional outcomes at school entry for children from lower compared to higher income families. Method: Data for this thesis were drawn from the Longitudinal Study of Australian Children, a national study following the health and development of a population-representative sample of children recruited in their first year of life (age range 3 to 19 months). The analytic approaches to answer the aims of this thesis included multiple imputation, regression, propensity score matching, effect measure modification, and the slope and relative index of inequality. Results: In the first study, more time in child care through the first three years of life was not associated with children’s receptive vocabulary ability but was associated with higher levels of parent-reported and teacher-reported externalising problem behaviours and lower levels of parent-reported internalising problem behaviours at age 4-5 years. These effects were concentrated among children who experienced predominately centre-based child care. In the second study, the quality of relationships in formal child care at age 2-3 years was associated with children’s task attentiveness, emotional regulation, receptive vocabulary, literacy and maths proficiency, internalising and externalising behaviours at age 4-5 years, and these effects, although weaker, continued to exert their influence at age 6-7 years after two years of formal schooling. The quality of activities in formal child care was only associated with children’s emotional regulation and there was no evidence that provider or program characteristics of care were associated with children’s developmental outcomes. In the third study, after adjusting for confounding, there was some evidence of effect measure modification on the additive and multiplicative scales of child care quality by income. Specifically, higher quality child care, in terms of relationships with child care providers, was more strongly associated with better cognitive and socio-emotional outcomes among children from lower income than those from higher income families, suggesting that higher quality child care matters more for lower income children. Conclusions: Findings from this thesis present the first comprehensive, longitudinal analysis of the type, time and quality of child care on children’s development using a nationally representative sample of children relevant to the Australian experience. The findings are consistent with overseas research showing that child care may influence children’s development in both positive and negative ways. Most notably, these findings suggest that higher quality relationships in child care support children’s positive cognitive and socio-emotional development at school entry, particularly in relation to children from disadvantaged backgrounds.
Keywords: Disadvantage, adversity and resilience; Childhood and child development; Learning, education and training